Role of transfection in the priming of cytotoxic T-cells by DNA-mediated immunization. - Sbai, H; Schneider, J; Hill, A; Whalen, R (2002)
DNA vaccination results in remarkably strong, broad-based immune responses to the encoded proteins and it is a simple and effective method of inducing cytotoxic T-lymphocyte (CTL) responses. Bone marrow-derived cells can take up and present exogenous antigenic protein liberated by transfected fibroblasts or myoblasts after the injection of such cells. In addition, dendritic cells can carry the injected plasmid DNA, supporting the hypothesis that dendritic cells can be directly transfected. It is, however, unclear from the current data what proportion of the cytotoxic immune response is initiated by the transfer of protein compared to that resulting from direct transfection of professional antigen presenting cells. This question is addressed here by using a matched series of plasmid DNA vectors expressing the wild-type or several mutant forms of HBsAg that are secretion-defective or severely truncated. The data indicate that neither HBsAg particle formation nor its secretion or liberation plays a significant role in the development of the cytotoxic immune response. The results argue that direct transfection of bone marrow-derived cells is the major, and possibly the only, mechanism used for priming of naive CTL precursors directed against the HBsAg.